The Effect Of Work Motivation And Work Discipline On Village Employee Performance In Baebunta District - Ines Febrian; Suparni Sampetan; Andi Rizkiyah Hasbi (LP2M IAIN Palopo, 2025)
This research was conducted on Village Employees in the Baebunta Sub-district. The study employs a quantitative approach aimed at testing and analyzing the influence of Work Motivation and Work Discipline on the Performance of Village Employees in the Baebunta Sub-district. The data collection techniques used in this research include primary data, secondary data, interviews, questionnaires, and observations. The total number of employees is 80, and a sample of 74 respondents was determined using the Slovin formula. The analytical method used is linear regression with two independent variables, analyzed using SPSS (Statistical Package for the Social Sciences) version 26. The results show that the X1 variable (Work Motivation) has a t-count value of 5.036, which is greater than the t-table value of 1.666, with a significance value (Sig.) of 0.000. Since the significance value is less than 0.05, it indicates a significant influence of work motivation on employee performance. Similarly, for the X2 variable (Work Discipline), the t-count is 1.972, also greater than the t-table value (1.666), with a significance value of 0.043. As 0.043 < 0.05, work discipline also significantly affects employee performance. Thus, both work motivation and work discipline individually have a significant impact on employee performance. The F-test results in a significant value (p-value < 0.05), with a significance level of 0.000 and an F-count of 32.795. Since the significance value is less than 0.05 and the F-count exceeds the F-table value of 2.37, it can be concluded that the independent variables collectively have a significant effect on the dependent variable.